Vitamin D Supplementation. Issue 18 (May 2015) - Drury, Rosalyn; Rehm, Andreas; Johal, Simran; Nadler, Robert; Mayr., Johannes
<x xml:space="preserve">Abstract</x> Abstract There is increasing concern that vitamin D deficiency poses a major health problem for children. Deficiency can cause hypocalcemic seizures, growth disturbances, and rickets and may influence diabetes, cardiovascular dysfunction, autoimmune diseases, and attention deficit hyperactivity disorders. Reduced vitamin D levels in children presenting to pediatric orthopedic services are common. In the United Kingdom, recommendations on vitamin D supplementation are set by the Department of Health (DoH) and the National Institute of Health and Clinical Excellence. These state that all children aged 6 months to 5 years ought to receive 7 to 8.5 μgof vitamin D daily. We carried out a survey of 203 parents attending our pediatric and pediatric orthopedic and fracture clinics to evaluate parental awareness of the DoH recommendations on vitamin D supplementation for children and to assess the extent to which children were receiving vitamin D supplements. About 85.71% of parents were not aware of the recommendations. Only 14.29% stated that they were aware of the benefits of vitamin D for their children and just 17.73% of children were receiving vitamin D supplementation; 17 via formula milk and 18 via multivitamin formulations. Parents are generally not aware about vitamin D supplementation because of a lack of information with the high rates of reported suboptimal vitamin D levels amongst children not being addressed resulting in increased health risks to our children. Major improvements are needed in the implementation of supplementation at all points of contact between parents and health-care professionals.